Expert system for medical diagnosis / Mahamad Farizan Mahamad - Mahamad, Mahamad Farizan (2004)
This paper will present a system that able to identify and monitoring the level of sickness of heart attack, diabetes and high blood pressure depending to the risk factors. Risk factors for this chronic disease are factors that do not seem to be a direct cause of the disease, but seem to be associated in some way. Having the risk factors for these diseases make more chances of getting a condition higher for Heart attack, Diabetes and Height Blood Pressure. The diagnosis process is based on the comparison of the risk factors that appear on a patient and medical result estimation depending to the percentage of risk factors occur.